Microcephaly in neonates of mothers with prenatal exposure to Zika virus. A systematic review (Boletin Médico de Postgrado, 2023)
A research was carried out with the aim of identifying the presence of microcephaly in neonates of mothers with prenatal exposure to Zika virus. The bibliographic search was carried out within the period November-December 2021, in full text and, English and Spanish languages, in Medline, LILAC, BVS, Cibertedis, Thesaurus, PubMed, Scielo, Elsevier, Science Direct, Academic Google and ResearchGate databases. Data were extracted using a data extraction form developed by the author that followed the recommendations described in the Cochrane Handbook of Systematic Reviews of Interventions (version 5.1.0). Information on the bibliometric characteristics of the articles, methodology (study design, sample year, means of publication) and conclusions was extracted. From this review it can be concluded that in the population studied microcephaly is most likely a result of congenital Zika virus infection classified as a neurotropic and teratogenic virus, however, more research is needed to better understand the possible implications of these findings.
Keywords: Zika virus; microcephaly; newborn; congenital abnormalities; systematic review